2014
DOI: 10.1088/0953-8984/26/39/393001
|View full text |Cite
|
Sign up to set email alerts
|

Image-potential states and work function of graphene

Abstract: Image-potential states of graphene on various substrates have been investigated by two-photon photoemission and scanning tunneling spectroscopy. They are used as a probe for the graphene-substrate interaction and resulting changes in the (local) work function. The latter is driven by the work function difference between graphene and the substrate. This results in a charge transfer which also contributes to core-level shifts in x-ray photoemission. In this review article, we give an overview over the theoretica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
45
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(60 citation statements)
references
References 109 publications
(205 reference statements)
6
45
1
5
Order By: Relevance
“…Although graphene might possess only a weak interaction with SiC, our results generally show that the shape of the image-potential states is very sensitive to the substrate-induced symmetry break even for large separations due to their large spatial extent. In another 2PPE experiment on graphene/SiC(0001), Shearer et al [42] indeed observed a single series of sharp symmetric peaks of image-potential states in agreement with data shown in [13]. Therefore, it seems rather unlikely that the experimentally found splitting of the first image-potential state on graphene/SiC [8,10] can be interpreted as a remnant of the mirror symmetry of freestanding graphene with a small energy separation between these two states.…”
Section: D Potential Experimentssupporting
confidence: 55%
See 1 more Smart Citation
“…Although graphene might possess only a weak interaction with SiC, our results generally show that the shape of the image-potential states is very sensitive to the substrate-induced symmetry break even for large separations due to their large spatial extent. In another 2PPE experiment on graphene/SiC(0001), Shearer et al [42] indeed observed a single series of sharp symmetric peaks of image-potential states in agreement with data shown in [13]. Therefore, it seems rather unlikely that the experimentally found splitting of the first image-potential state on graphene/SiC [8,10] can be interpreted as a remnant of the mirror symmetry of freestanding graphene with a small energy separation between these two states.…”
Section: D Potential Experimentssupporting
confidence: 55%
“…It has been argued that these states are remnants of the first even and odd state of freestanding graphene even if its mirror symmetry is in fact broken due to the presence of the substrate. In contrast to these findings, only a single series of image-potential states has been observed on weakly interacting graphene/metal systems [11][12][13][14]. For other metals, like Ni, Pd, Rh, and Ru, the interaction between graphene and the metal can be much stronger.…”
Section: Introductionmentioning
confidence: 83%
“…Several recent experiments have taken advantage of these exposed surface states of crystalline metal substrates for such studies. [4][5][6][7] On Cu(111), an occupied Shockley surface state forms in the projected band gap leading to a quasi-2D electron gas, 8 which can act as a sensitive probe of changes in the surface electronic potential. Additional unoccupied surface states form due to the potential well created by an electron and its image charge.…”
mentioning
confidence: 99%
“…Image potential states (IPS) on metallic surfaces [6][7][8][9][10][11][12] resembling Rydberg series were observed on several topological insulators [13][14][15][16][17], with the energy states lying slightly below the vacuum level. Angle-resolved two-photon photoemission (2PPE) studies of Bi 2 Te 2 Se surfaces reported on the first IPS to be at E = 4.5eV above Fermi level [15].…”
Section: Introductionmentioning
confidence: 99%
“…IPS are weakly coupled to the bulk in comparison to the other surface states. The image potential states of TIs have relatively long lifetimes in the order of fs, comparable to metallic surfaces [12]. In Scanning Tunneling Spectroscopy (STS), IPS are detected as Gundlach oscillations, which is a phenomenon of field emission resonance through IPS in the tip-sample gap [18].…”
Section: Introductionmentioning
confidence: 99%